Mindfulness as a Weight Loss Treatment for Veterans - Stanton, Michael V.; Matsuura, Justin; Fairchild, Jennifer Kaci; Lohnberg, Jessica A.; Bayley, Peter J. (Frontiers in Nutrition, 2016)
Despite substantial evidence for their effectiveness in treating disordered eating and obesity, mindfulness-based treatments have not been broadly implemented among Veterans. A number of reviews have reported mindfulness to be beneficial in promoting healthy eating behaviors and weight loss among non-Veteran samples. We discuss this approach in the context of the Veterans Affairs system, the largest integrated healthcare provider in the United States and in the context of Veterans, among whom obesity is at epidemic proportions. In this article, we discuss what is known about treating obesity using a mindfulness approach, mindfulness interventions for Veterans, a new pilot mindfulness-based weight loss program designed for Veterans, and future directions for this type of obesity treatment in Veterans. We conclude that this population may be uniquely poised to benefit from mindfulness-based treatments.